Design and development of a portable radio telescope - Lim, Wei Gie (2018)
Building a simple radio telescope is relatively easy with a combination of persistence and the proper help. Once radio telescope has been developed, which can be easy build in schools and tertiary institutions make students to further interest in science and technology. Surplus satellite television equipment can be modified to permit radio observe the Sun and the Moon, it can be able to allow the user to learn the fundamentals of radio astronomy. Radio telescope is an astronomical instrument consisting of a radio receiver and an antenna system that is used to detect radiofrequency radiation emitted by the Sun. As radio-wave wavelengths are much longer than those of visible light, radio telescopes have to be very large physically in order to attain the resolution of optical telescopes. A solar flare is a tremendous explosion on the Sun that happens when energy stored in the Sun’s “twisted” magnetic field is suddenly released. With a radio telescope we can detect solar flare activities. The most important conclusion is that the site is, in terms of its engineering properties, certainly suitable for conducting radio astronomy.